Distribution characteristics of endophytic bacteria and endophytic nitrogen-fixing bacteria in Vicia faba root nodules in Rocky desertification areas of Southwest China - Jinhua Wang; Zichang Liu; Ziyun Yang; Bo Yang; Wuxian Zhang (Scientific Reports)
Abstract Understanding bacterial communities in leguminous root nodules is crucial, as leguminous plants are key pioneer species for restoring degraded soil ecosystems. This study collected root nodule samples from wild Vicia faba across four rocky desertification (RD) sites in Honghe, Yunnan, China. The diversity of endophytic bacteria, including nitrogen-fixing bacteria, in these nodules was analyzed using 16 S rDNA and nifH gene sequencing. A total of 451 bacterial Operational Taxonomic Units (OTUs) were identified, with Pseudomonadota as the dominant phylum and Pseudomonas and Rhizobium as the predominant genera. Notably, bacterial community composition varied significantly among the four areas. Rhizobium was positively correlated with available phosphorus content and RD degree but was negatively correlated with soil water content (SWC). These findings indicate that available phosphorus, RD degree, and SWC are key factors influencing the endophytic bacterial community in Vicia faba root nodules. A total of 309 OTUs representing nitrogen-fixing bacteria were identified; again, Pseudomonadota was dominant, with Bradyrhizobium and Rhizobium being most prevalent. Significant variations in nitrogen-fixing bacterial communities occurred across sampling sites. Key physicochemical factors affecting this community’s structure included total phosphorus, total nitrogen, and pH. These results may provide a theoretical basis for developing biological control strategies to mitigate RD.